OFOBS Seafloor images from the margins of the Atacama Trench, collected during RV SONNE cruise SO261 - Laura Hehemann; Autun Purser; Ulrich Hoge; Frank Wenzhöfer (PANGAEA, 2018)
The Ocean Floor Observation and Bathymetry System (OFOBS) was used during the SO261 cruise to the Atacama Trench, Chile, to image the seafloor at 4,000 - 6,000 m depth, on the eastern and western margins of the trench. The OFOBS system consisted of a towed underwater camera system equipped with both a high-resolution photo-camera (iSiTEC, CANON EOS 5D Mark III) and a high-definition video-camera (iSiTEC, Sony FCB-H11) as well as an intergrated sidescan sonar system. The cameras were mounted on a steel frame (140L x 92W x 135H cm), together with two strobe lights (iSiTEC UW-Blitz 250, TTL driven), three laser pointers spaced with a distance of 50 cm used to estimate the size of seafloor structures, four LED lights, and a USBL positioning system (Posidonia) to track the position of the OFOBS during deployments, with additional positioning information provided by the newly integrated INS and DVL systems. In automatic mode, a seabed photo, depicting an area of approximately 4 m**2, with variations depending on the actual height above ground, was taken every 15 seconds to obtain series of "TIMER" stills distributed at regular distances along the profiles that vary in length depending on duration of the cast. At a ship speed of 0.5 kn, the average distance between seabed images was approximately 5 m. Ship speed was however greatly influenced by ice conditions. Additional "HOTKEY" photos were taken from interesting objects (organisms, seabed features, etc) when they appeared in the live video feed. During this cruise there was considerable interest in sampling with MOCHNESS trawl from within the water column. In light of this, the seafloor images in this dataset are bracketed in some cases with images collected from within the water column, at the request of the cruise participants.